2019
DOI: 10.1007/s12350-017-0893-0
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine stress myocardial perfusion imaging in octogenarians: Safety, tolerability, and long-term prognostic implications of hemodynamic response and SPECT-related variables

Abstract: In octogenarians, adenosine stress MPI is well tolerated and provides effective long-term risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
2
1
0
1
Order By: Relevance
“…In this issue of the Journal, the article by Katsikis et al presents the results of a study evaluating the tolerability, safety, and prognostic value of adenosine MPS in 370 patients aged 80-89 years. 5 As the authors rightly pointed out, tolerability to adenosine stress was similar to that reported in a previous series of younger subjects with a slightly larger proportion of octogenarians completing a full 6-minute adenosine infusion protocol (84% vs. 80%). 6 This finding is not surprising.…”
supporting
confidence: 79%
“…In this issue of the Journal, the article by Katsikis et al presents the results of a study evaluating the tolerability, safety, and prognostic value of adenosine MPS in 370 patients aged 80-89 years. 5 As the authors rightly pointed out, tolerability to adenosine stress was similar to that reported in a previous series of younger subjects with a slightly larger proportion of octogenarians completing a full 6-minute adenosine infusion protocol (84% vs. 80%). 6 This finding is not surprising.…”
supporting
confidence: 79%
“…When comparing these two groups, octogenarians had more severe and extensive myocardial ischemia, while coronary artery disease (CAD) was more pronounced and diffuse. Like in previous investigations, [2][3][4][5][6][7] octogenarians had a significantly higher major adverse cardiac event rate than in younger patients during a mean follow-up period of 32 months. Notably, in the current retrospective analysis, 1 the diagnostic accuracy of MPS was similar among both groups (area under the curve (AUC) for, e.g., two or three vessel disease: 0.54 vs 0.58), while the prognostic accuracy was higher or comparable between octogenarians and the younger group for death (hazard ratio (HR):10.7 vs 2.72), myocardial infarction (HR: 1.06 vs 1.24), or their combination (HR: 4.93 vs 1.87).…”
supporting
confidence: 73%
“…Assim, em pacientes com suspeita ou doença coronária crônica comprovada, a estimativa da quantidade de miocárdio em risco, avaliada por análises semi e quantitativa do número, extensão, intensidade e grau de reversibilidade dos defeitos existentes, bem como a medida da FEVE pósestresse físico ou após provas farmacológicas provocativas, têm valor prognóstico, indicando risco de eventos no seguimento clínico. [134][135][136][137][138] Outros marcadores cintilográficos de gravidade podem ainda ser destacados, como a dilatação transitória aparente do VE, induzida ou acentuada por exercício ou provas farmacológicas, 139,140 podendo traduzir isquemia subendocárdica extensa, além de hipercaptação pulmonar, na tradução de disfunção ventricular esquerda. Adicionalmente, o aumento da captação nas paredes do ventrículo direito (VD) em pacientes multiarteriais, com predomínio de lesões em território de coronária esquerda, pode sugerir desbalanço das perfusões entre os ventrículos.…”
Section: Valor Do Binômio Diagnóstico -Prognóstico Na Avaliação Integunclassified